DAZ 4 ZOE - Swindells, Robert (Penguin Group, 1992)
Fifteen year old Daz lives in the inner city, a fenced and impassable ghetteo of despair and decay for inhabitants called Chippies. Zoe is a Subby, living in an outer-ring suburb of conformity and boredom. How the two teenagers meet and keep contact across the divide is nail-biting enough, but the story of their escape from the forces is brilliant, pulling few punches about the cost to others which their freedom must exact.'
Keywords: Juvenile Fiction